Pengaruh Faktor Internal dan Faktor Eksternal terhadap Manajemen Pajak - Wardani, Dewi Kusuma; Setiya Putri, Hany Nur (AKMENIKA, 2018)
This research aims to analyze the impact of profitability,capital structure,fixed asset intensity,and economic growth towards tax management using effective tax rates as a indicator in Real Estate and Property companies in the period 2011-2014. We used the secondary data from IDX and BPS of Product Domestic Bruto. Multiple regression analysis is was the method of analysis used. The sampling technique used in this research was purposive sampling method and obttained 96 samples of data for 24 companies. The regression test results showed that profitability has a significant positive effect to tax management, capital structure has a significant negative to tax management. While, for the fixed asset and economic growth does not effect on the tax management.